Internal Audit Capability and Recurring Audit Findings in Government Departments - Qanga Enathi; Awonke Geqeza (JURNAL AKUNTANSI DAN AUDITING, 2026)
Recurring audit findings remain one of the greatest governance challenges confronting South African government departments. Despite legislative requirements mandating the establishment of internal audit functions, many public institutions continue to receive qualified, adverse and disclaimer audit opinions year after year. The study is grounded in Internal audit capability model, agency theory and institutional theory. This study adopted a qualitative documentary research design and exclusive use of secondary data obtained from the Auditor-General South Africa's General Reports for the past 5 years (2021 to 2025) on National and Provincial Government. The results revealed persistent weaknesses in internal controls; ineffective implementation of audit recommendations; leadership and accountability failures; inadequate internal audit capability; and weak oversight by governance structures. The paper concludes by proposing policy interventions aimed at strengthening internal audit capability as a strategy for improving audit outcomes and public sector governance.